2004
DOI: 10.1128/jcm.42.2.700-706.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization and Antibiotic Resistance of Campylobacter jejuni Isolated from Meats, Water, and Humans in Sweden

Abstract: The incidence of Campylobacter jejuni has increased during the last decade, and today it is the leading cause of bacterial enteritis in most developed countries. Still, there is a lack of knowledge about infection routes and to what extent identified sources are responsible for spreading the bacterium to humans. The major objective of this work was to explore the genetic similarity between C. jejuni isolated from different sources. C. jejuni isolated from patients (n ‫؍‬ 95), five types of meat (n ‫؍‬ 71), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
23
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 28 publications
6
23
1
Order By: Relevance
“…SmaI digestion, while less discriminatory, is sufficient in many cases to demonstrate that isolates are different. We believe that to demonstrate similarity, or that isolates are indistinguishable, digestion with two enzymes is essential, a finding also supported by other researchers (20,27,31 Epidemiological analysis. In this study, 90% of isolates could be linked retrospectively to notified campylobacteriosis cases, which is a rate 10% higher than that reported previously in the Auckland area of New Zealand (33).…”
Section: Discussionsupporting
confidence: 55%
“…SmaI digestion, while less discriminatory, is sufficient in many cases to demonstrate that isolates are different. We believe that to demonstrate similarity, or that isolates are indistinguishable, digestion with two enzymes is essential, a finding also supported by other researchers (20,27,31 Epidemiological analysis. In this study, 90% of isolates could be linked retrospectively to notified campylobacteriosis cases, which is a rate 10% higher than that reported previously in the Auckland area of New Zealand (33).…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, KpnI cleavage reduced the number of poultry isolates with a pulsotype matching that of a patient isolate from 69 to 41. This degree of overlap between pulsotypes of human and chicken isolates is similar to previously reported values (14,18).…”
supporting
confidence: 78%
“…The evidence for genetic stability is also supported by the results of a Finnish study, which found the same PFGE profiles in strains collected in three different years (11). Similarly, the major PFGE groups in the present study were also found in an earlier Swedish study that analyzed 177 isolates collected in 2000 from retail meat products (mostly chicken), patients, and water (18). In fact, the five major PFGE groups from that study were all among the six largest groups in the Campy-SET study.…”
supporting
confidence: 68%
See 2 more Smart Citations